Lost in translation: The need for updated messaging strategies in invasion biology communication - Rachel A. Reeb; J. Mason Heberling (Plants, People, Planet)
Societal Impact Statement As with any complex environmental challenge, information about the “invasive species problem” must be communicated effectively to generate widespread public trust, understanding, and engagement in solutions. However, there is growing recognition that conventional messaging strategies can be ineffective or even detrimental at activating the broader public. Flawed communication practices can have harmful societal impacts by perpetuating misinformation, propagating feelings of panic and fatalism, and disaffecting audience members within historically marginalized communities. In this article, we draw attention to existing communication barriers in invasion biology and attempt to address the flawed messaging strategies which perpetuate negative societal outcomes. Summary Effective communication about introduced, invasive species is necessary for the public to engage in productive dialogue and participate in solutions. Best practices in communication are more essential than ever before, as the harmful environmental and societal impacts of invasive species are exacerbated by globalization and anthropogenic disturbance. In this article, we review how public misunderstanding and mistrust present persistent barriers to invasion biology communication. We then describe three flawed messaging strategies that underlie these barriers. These strategies include fear appeals, simplified invasion metaphors, and militaristic and xenophobic language. Though intended to inspire a public sense of urgency and action, these strategies more often stoke sentiments of confusion and mistrust when employed in practice. Efforts to develop new best practices in communication are already underway. However, there is a great need for efficacy testing and wider adoption among science and education professionals alike. We draw from the interdisciplinary literature to recommend specific forms of value appeals, metaphors, and language that are a promising foundation for improvement.